Peran Kejaksaan dalam Pemberantasan Tindak Pidana Korupsi Desa di Indonesia - I Made Agus Mahendra Iswara; Ketut Adi Wirawan (Fakultas Hukum, Universitas Warmadewa, 2020)
This study aims to determine the role of the prosecutor's office in eradicating criminal acts of village corruption in Indonesia. The method used in this research is a type of normative legal research with the aim of outlining issues to be further discussed based on legal theory and then related to applicable laws and regulations. The results of this analysis indicate that referring to the Law on Prosecution that the Prosecution has a role in combating corruption in the criminal field (in this case village corruption), namely conducting investigations, investigations, prosecutions and case executions. Besides that, in the case of preventive efforts, intelligent Pidsus, Special Crimes Section, facilities were formed, for example the formation of several task forces (task force) with specific tasks in this case related to the prevention of village corruption. In addition, the Intelligence Intelligent was also established covering intelligence, investigation, security, and raising activities to prevent criminal acts to support law enforcement both preventive and repressive in the fields of ideology, politics, economics, finance, social culture, defense and security, implementing deterrence against people certain and / or participate in organizing public order and peace